The Role of Ideology in Terrorist Attack Intentions and Outcomes - Carson, Jennifer Varriale (Terrorism and political violence, 2024)
This study seeks to investigate whether ideological elements, namely that of audience and othering, are related to attack-level objectives and effects. Prior research has established a strong connection between ideological subscription and violent attack outcomes, but few studies have sought to examine the full spectrum of ideologies. Moreover, little empirical attention has been given to examining how ideological affiliation may correlate with violent intentions in terrorist attacks; namely, an actor’s intention to kill or commit a mass casualty incident. To address these research gaps, we pose the question: Is a U.S. terrorist attack’s ideological component correlated with its both intentions and outcomes? Utilizing a sample of 2,275 terrorist incidents from the Global Terrorism Database (GTD), we examine our research question through a series of models with sensitivity checks using logistic regression and zero-inflated negative binomial analyses. In sum, our results are consistent with the premise that ideology does matter, particularly if this ideology involves a defined other.